Investigating the role of employee psychological well-being and psychological empowerment with relation to work engagement and sustainable employability. Issue 2 (16th December 2021) - Rahi, Samar
Abstract : Purpose: This study aims to gain insight into how employee psychological and human resource (HR) practices impact employee work engagement behavior. In addition to that, the research model of this study has tested the moderating relationship of affective employee commitment between employee work engagement and sustainable employability. Design/methodology/approach: The research model is empirically tested with data set of 311 responses retrieved from an employee working in private organizations. Sample size of this study is computed with prior power analysis. Data were analyzed with partial least square-based structural equation modeling (SEM). Findings: Findings of the SEM revealed that altogether psychological well-being, psychological empowerment, HR compensation, HR training, transformational leadership and job enrichment have explained R 2 66.1% variance in employee work engagement. Concerning individual impact size psychological well-being has shown medium level effect size ( f 2 ) in measuring employee work engagement. However, all other exogenous variables have shown a small effect in determining employee work engagement. The moderating effect of commitment is confirmed in such a way that the relationship between employee work engagement and sustainable employability will be higher when affective commitment is higher. Practical implications: This research has synthesized HR literature into four core dimensions of HR practices and, hence contributes to HR literature. Similarly, this research contributes to well-being theory while integrating employee psychological well-being into the research model. For HR practitioners this research revealed that psychological well-being, psychological empowerment, affective employee commitment, transformational leadership, HR compensation and HR training are core factors, which influence employee behavior toward work engagement and sustainable employability. Originality/value: The current research is unique as it investigates sustainable employability phenomenon with an integrated research model that combines employee psychological and HR factors. The concept of sustainable employability is less studied, and therefore this research fills the research gap in this context.